2020
DOI: 10.1063/1.5131854
|View full text |Cite|
|
Sign up to set email alerts
|

Large memcapacitance and memristance at Nb:SrTiO3/La0.5Sr0.5Mn0.5Co0.5O3-δ topotactic redox interface

Abstract: The possibility to develop neuromorphic computing devices able to mimic the extraordinary data processing capabilities of biological systems spurs the research on memristive systems. Memristors with additional functionalities such as robust memcapacitance can outperform standard devices in key aspects such as power consumption or miniaturization possibilities. In this work, we demonstrate a large memcapacitive response of a perovskite memristive interface, using the topotactic redox ability of La0.5Sr0.5Mn0.5C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The device presents retention times for both resistive states of at least 10 4 s (not shown here). From the analysis and modelling of dynamic I-V curves, we showed that the memristive behavior originates at the NSTO/LSMCO interface upon oxidation/reduction of LSMCO [24]. We have successfully simulated the experimental HSL by assuming that LSMCO is in contact with an oxygen reservoir that allows the necessary oxygen release and uptake for the topotactic redox behavior, as shown in Ref.…”
Section: Characterization Of Voltage-controlled Devicesmentioning
confidence: 87%
See 4 more Smart Citations
“…The device presents retention times for both resistive states of at least 10 4 s (not shown here). From the analysis and modelling of dynamic I-V curves, we showed that the memristive behavior originates at the NSTO/LSMCO interface upon oxidation/reduction of LSMCO [24]. We have successfully simulated the experimental HSL by assuming that LSMCO is in contact with an oxygen reservoir that allows the necessary oxygen release and uptake for the topotactic redox behavior, as shown in Ref.…”
Section: Characterization Of Voltage-controlled Devicesmentioning
confidence: 87%
“…A very interesting topotactic redox perovskite is La 1/2 Sr 1/2 Mn 1/2 Co 1/2 O 3−x (LSMCO), which displays and oxidized -more conducting-phase with x = 0 and a rhomboedral R 3c structure, as well as a reduced -more resistive-phase with x =0.62 and an orthorombic Pbnm structure [23]. We have shown [24] that epitaxial Nb:SrTiO 3 /LSMCO structures display a robust memristive behavior concomitant with a memcapacitive effect -reversible change in the capacitance between different non-volatile states [25][26][27][28][29][30][31][32][33]-. The memcapacitance found in this system -C HIGH /C LOW ≈ 900 at 10 kHz and ≈ 100 at 150 kHz-was the highest reported to date by a factor of ≈ 10 and originates at the NSTO/LSMCO interface, where a switchable p-n diode is formed [24].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations